2017
DOI: 10.2174/1872214810666161020154905
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Roles of Mitogen-Activated Protein Kinase (MAPK) Pathways in Health and Diabetes: Lessons Learned from the Pancreatic β-Cell

Abstract: The MAPK pathways are activated in the presence of various stress stimuli including intracellular ROS, via distinct signaling cascades. Once activated, MAPKs participate in specific intracellular signaling processes via interaction with several downstream kinases including the MAPKactivated protein kinases (MAPKAPKs) and transcription factors including c-jun and p53. We have provided an overview of existing evidence in the islet β-cell on the regulatory roles of these MAPKs in mediating cellular responses to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 90 publications
0
35
0
1
Order By: Relevance
“…While p38 and JNK, known as stress-activated protein kinase, are strongly activated by various cellular stresses, such as heat shock and oxidative stress, TNF-α and LPS, which play roles in cell proliferation and survival, are associated with the induction of apoptosis by cellular stresses [30]. In the present study, p38 and JNK phosphorylation occurred after cells were treated with LPS for 12 h. The major functional role of phosphorylated p38 and JNK lies in mediating the downstream substrates involved in the cell cycle and apoptosis [29]. Our results also suggest that the relative mRNA expressions of downstream genes of the p38 and JNK signaling pathways, including AP-1, ATF-2, ELK-1, and p53, were increased and that Stat3 expression was dramatically decreased after cells were treated with LPS, which may activate caspases and induce apoptosis [31, 32].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…While p38 and JNK, known as stress-activated protein kinase, are strongly activated by various cellular stresses, such as heat shock and oxidative stress, TNF-α and LPS, which play roles in cell proliferation and survival, are associated with the induction of apoptosis by cellular stresses [30]. In the present study, p38 and JNK phosphorylation occurred after cells were treated with LPS for 12 h. The major functional role of phosphorylated p38 and JNK lies in mediating the downstream substrates involved in the cell cycle and apoptosis [29]. Our results also suggest that the relative mRNA expressions of downstream genes of the p38 and JNK signaling pathways, including AP-1, ATF-2, ELK-1, and p53, were increased and that Stat3 expression was dramatically decreased after cells were treated with LPS, which may activate caspases and induce apoptosis [31, 32].…”
Section: Discussionmentioning
confidence: 62%
“…ERK1/2 are mostly activated by growth factors, such as epidermal growth factor and nerve growth factor, which play central roles in the control of cell proliferation [29, 30]. While p38 and JNK, known as stress-activated protein kinase, are strongly activated by various cellular stresses, such as heat shock and oxidative stress, TNF-α and LPS, which play roles in cell proliferation and survival, are associated with the induction of apoptosis by cellular stresses [30].…”
Section: Discussionmentioning
confidence: 99%
“…Post‐translational prenylation of small G‐proteins (Ras, Rho, Rac1, Cdc42, Rap1 and Rabs) is critical for GSIS to occur. It should be noted that tonic increase in Nox2‐mediated generation of ROS appears to favour cytoskeletal remodeling and activation of ERK1/2 signalling modules while suppressing stress kinases such as JNK1/2 (Figure ) . Interestingly, however, metabolic stress condition (glucotoxicity, lipotoxicity and ER stress) promotes sustained activation of Rac1, which, in turn, accelerates the Nox2‐ROS‐stress kinase signalling pathway leading to mitochondrial dysfunction, loss in GSIS and apoptotic demise of the islet β‐cell (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sustained activation of Nox2 results in increased levels of ROS, which, in turn, promote Rac1‐induced activation of apoptotic JNK1/2, and inhibit ERK1/2 signalling pathways. Additional studies are needed to further validate this model (Reproduced with permission from Bentham‐Science)…”
Section: Discussionmentioning
confidence: 99%
“…In some tissues, Plin5 has been reported to involve in the regulation of PI3K/Akt or MAPK pathways (p38 MAPK, ERK, and JNK) (21,24,40,44,49), which is the upstream modulators of Nrf2 in pancreatic β-cells (39,41). As evidenced by prior studies, excess ROS production and oxidative stress results in the activation of apoptotic p38 MAPK and JNK signaling, whereas activation of antiapoptotic PI3K/Akt and ERK pathways facilitates the translocation of Nrf2 into the nucleus, thereby activating the Nrf2/ARE pathway and alleviating oxidative damage (50,51). In the current study, p38 MAPK and JNK pathways were found to be activated but PI3K/Akt and ERK pathways were inhibited in β-cells under palmitate inducedoxidative stress.…”
Section: Discussionmentioning
confidence: 95%